2017
DOI: 10.1007/s00284-017-1248-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity of Type B3 Bacteriophages of Caulobacter crescentus

Abstract: The genomes of the type B3 bacteriophages that infect Caulobacter crescentus are among the largest phage genomes thus far deposited into GenBank with sizes over 200 kb. In this study, we introduce six new bacteriophage genomes which were obtained from phage collected from various water systems in the southeastern United States and from tropical locations across the globe. A comparative analysis of the 12 available genomes revealed a “core genome” which accounts for roughly 1/3 of these bacteriophage genomes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This exceptionally small plaque size produced by Kronos counters the typical inverse relationship of plaque size to genome size among caulophages. For example, giant caulophages that possess larger genomes such as phiCbk (205 kbp) and Colossus (297 kbp) produce small plaques (1 mm) [3,14]. In contrast, caulophages with small genomes (40-50 kbp) and small capsid sizes (< 60 nm), such as Lullwater [20] produce variable-sized larger plaques (1-3.5 mm).…”
Section: Phage Isolation and Characterizationmentioning
confidence: 99%
“…This exceptionally small plaque size produced by Kronos counters the typical inverse relationship of plaque size to genome size among caulophages. For example, giant caulophages that possess larger genomes such as phiCbk (205 kbp) and Colossus (297 kbp) produce small plaques (1 mm) [3,14]. In contrast, caulophages with small genomes (40-50 kbp) and small capsid sizes (< 60 nm), such as Lullwater [20] produce variable-sized larger plaques (1-3.5 mm).…”
Section: Phage Isolation and Characterizationmentioning
confidence: 99%
“…Sequencing produced a circular assembly with a length of 104,206 bp. The large genome is consistent with its B3 morphotype [ 25 ], and the extremely prolate capsid of an enlarged size is able to carry a larger genome than its icosahedral counterpart. The first 10,992 bp were determined to be a direct terminal repeat (DTR), with a 434.36 ± 68.26× sequencing coverage that was approximately 2-fold greater than that of the rest of the genome (230.88 ± 28.14×) ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Plaques of phage RXM are clear and round, with a well-defined boundary ranging from 1.5 to 1.8 mm in diameter ( Figure 1 A). TEM inspection revealed that RXM displays a unique Siphoviridae B3 morphotype [ 25 ], with a prolate capsid (111.50 ± 1.48 nm long and 56.02 ± 3.06 nm wide) and a long flexible tail (220.57 ± 3.88 nm long). Intriguingly, TEM showed that virions often adhere to each other through their heads ( Figure 1 B; see also Supplementary Figure S1A and S1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Predicted functions are only available for genes 71 and 95; AAA ATPase and ThyX respectively. The RcD homologs of RcZahn 37-41 are in the same order in RcZahn and are in the highly conserved region on the left side of the genome (RcD genes [10][11][12][13][14]. Another gene encoding an ADP ribosyltransferase is present in RcZahn (gene 101) and in 6 of the 8 RcD phages but is absent from RcMcDreamy and RcSalem.…”
Section: Rcd Clustermentioning
confidence: 99%